Representation of the linguistic and cultural type of «ECO-ACTIVIST» in modern English-language media - L. S. Samsonova; V. D. Shevchenko (Вестник Самарского университета: История, педагогика, филология)
The article focuses on some of the results of the study of linguocultural types as composite images that exist in society. Linguocultural types (LCT) are significant for research within modern sociolinguistics and linguistic culture studies, as they express the common beliefs and values of society. The object of study is the linguocultural type «ECO-ACTIVIST». This choice is linked to the particular social significance of eco-activists for contemporary society. The authors of the article are especially interested in the positive and negative characteristics of the chosen LCT. They employ a combination of methods, including linguistic and cultural analysis and modeling of LCTs, and highlight the characteristics of «savior» and «terrorist» which are dominant for this LCT.